Development of Accounting E-module Based on Contextual Learning to Increase Student Interest in Learning - Kusumadyahdewi, Kusumadyahdewi; Lestari, Yona Octiani; Ramadhani, Farah (Universitas Negeri Malang, 2024)
This research aims to develop an accounting e-module for contextual-based learning to increase students' interest in accounting. This contextual learning connects accounting with the application of financial literacy, particularly in financial planning. The development research method utilizes the ADDIE development procedure model. Validation by media, material, and language experts, as well as feasibility trials, targets students from the class of 2022/2023 of the Social Sciences Education Study Program (Program Studi Pendidikan Ilmu Sosial - PIPS) at UIN Maulana Malik Ibrahim. Interest was measured using a questionnaire administered to both the experimental and control classes. The research results indicate that the interest of the experimental class was higher than that of the control class, demonstrating the effectiveness of using contextual-based e-modules in learning.